Puzzles in the Chinese Stock Market - Fernald, John; Rogers, John H. (The Review of Economics and Statistics, 2002)
Many companies on China's stock markets have traditionally had separate, restricted classes of shares for domestic residents and foreigners. These shares are identical other than for who can own them, but foreigners have generally paid only about one-quarter the price paid by domestic residents. We argue that the generally higher level (and volatility) of domestic share prices is consistent with the simplest asset pricing model, assuming plausible differences-about four percentage points-in expected rates of return by foreign and domestic investors. We attribute low Chinese expected returns to the limited alternative investments available in China. We then estimate how various company characteristics (including capital asset pricing model (CAPM) betas, company size, market liquidity, and other characteristics) affect the relative price paid by foreigners in a panel of companies. We find, for example, that foreigners pay a lower relative price for companies with a higher proportion owned by the state-reflecting, surprisingly, a higher absolute price paid by both foreigners and domestic residents.